Experiences of school counselors working in district boarding schools. Issue 2 (3rd April 2018) - Atli, Abdullah
ABSTRACT: The objective of this qualitative study is to discover the experiences of district boarding school counselors while conducting psychological counseling and guidance services. Within this framework, data were collected through phone interviews that were conducted with 12 school counselors who were employed in district boarding schools in Eastern and Southeastern Anatolia regions in Turkey. Study data were collected with a semistructured interview form designed to identify the professional experiences of district boarding school counselors. Overall findings indicated that the workload of school counselors was affected by the level of homesickness and risky behavior exhibited by the students. Furthermore, being a school counselor in district boarding schools was described as a process of performing counseling services (despite occasional experiences of occupational role conflicts), of not being able to receive sufficient parent support, and of experiencing the critical significance of cooperation with teachers and school administration.